Effect of Slow Music on Selected Cardiorespiratory Parameters among Stressful Young Individuals (Journal of Chittagong Medical College Teachers' Association, 2023)
Background: Stress is an unavoidable universal phenomenon in modern life. Music reduces stress. Music is used by therapist, psychologists and psychiatrist as a therapeutic intervention. It has beneficial and therapeutic effects on cardiac and respiratory function in normal and diseased subjects. It probably works by modification of autonomic nervous system centrally. This study was done with the objective to assess the effects of music intervention on cardio-respiratory function in young individuals leading a stressful life.  Materials and methods: This experimental study was conducted in the Department of Physiology, Chittagong Medical College, Chattagram. Total 60 subjects of first year MBBS, with equal number of male and female, studying in Chittagong Medical College, Chattagram, were included by stratified random sampling method according to inclusion and exclusion criteria. A questionnaire along with general information, about previous diseases, medical and family history were filled up by the subjects. Physiological parameters-pulse, systolic and diastolic blood pressure, Respiratory Rate (RR) and oxygen saturation (SPO2) were recorded before and after 15 minutes of music intervention for 15 days.  Results: Result was compiled and compared after data collection by using SPSS-25. Paired ‘t’-tests were done to compare differences between pre and post-intervention values of different outcome parameters. p